Molecular oxygen sensing: implications for visceral surgery - Kiss, Judit; Kirchberg, Johanna; Schneider, Martin (Langenbeck's archives of surgery, 2012)
BackgroundSince mammalian cells rely on the availability of oxygen, they have devised mechanisms to sense environmental oxygen tension, and to efficiently counteract oxygen deprivation (hypoxia). These adaptive responses to hypoxia are essentially mediated by hypoxia inducible transcription factors (HIFs). Three HIF prolyl hydroxylase enzymes (PHD1, PHD2 and PHD3) function as oxygen sensing enzymes, which regulate the activity of HIFs in normoxic and hypoxic conditions. Many of the compensatory functions exerted by the PHD-HIF system are of immediate surgical relevance since they regulate the biological response of ischemic tissues following ligation of blood vessels, of oxygen-deprived inflamed tissues, and of tumors outgrowing their vascular supply.PurposeHere, we outline specific functions of PHD enzymes in surgically relevant pathological conditions, and discuss how these functions might be exploited in order to support the treatment of surgically relevant diseases.